(3cJGH fUjMI Gdedhcs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi EfYGeg hCaVGdg hHYO aEfg SCdfi HYV GdcHQG hGdeJbOejf Cf Cfbd gPG GdcJGH fUjMI Gdedhc ef GddZI GdaGQSjI Edi GdCdaGX GdYQHjI s
(3BNQgG (B:s
(3acdeG jfGd GdQLd ef GdHdGA hGdgdGc hGdeMf aHSHH GdfSGA ceG bGd GdTGYQ (B: (3ef aJfI GdfShGf bO jYUi GdaJi GdQMef Ch jNjKi ef GdSdWGfi cd GdHdGA ef gf jCJi hGdhaGA efgf dG jCJi eOG GdCReGf Je GdcJGH hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1958s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs